Strategy in Handling Problem Financing at PT. Bank Sumut Syariah KCPSY Karya - Dwi Regina Erni; Mustafa Kamal Rokan (Penerbit Jurnal Indonesia, 2022)
Banking is one of the financial institutions that play an important role in the economy of a country. One of the current economic developments in Indonesia is the emergence of shariabased financial institutions, one of which is Islamic banking. Like the function of banking itself, namely as an intermediary institution between people who need capital and people who have excess capital. One of the Islamic banking facilities is financing, namely the distribution of funds from banks to customers who need working capital. The bank will provide capital to customers as business capital whose business results will be calculated for the results according to the agreement. However, in reality, in this financing, it is not uncommon for customers to experience default on installment payments. One of the causes of non-financing itself is due to business conditions that may decline. To minimize the risk of bad financing itself, banks must be able to create clear regulations. In this article, we will discuss the various strategies carried out by the Bank SUMUT Syariah Karya Medan in dealing with bad financing.